Pengaruh Pola Asuh Otoriter Orang Tua Dan Regulasi Emosi Terhadap Sibling Rivalry Pada Remaja Di Kecamatan Tebet. - Meielsa Dewi, Nindi; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study is a quantitative research aimed at examining the influence of authoritarianparenting styles and emotional regulation on Sibling Rivalry among adolescents in the Tebet sub -district. The sampling technique employed is accidental sampling. The participants in this studycomprised 100 respondents, a result obtained from the Slovin formula calculation. Data collectionin this research utilized three scales: the Sibling Rivalry scale, the Authoritarian Parenting scale,and the Emotional Regulation scale. The Sibling Rivalry scale consists of 17 items with itemdiscrimination values ranging from 0.303 to 0.588 and a reliability coefficient of 0.639. The datawere analyzed using Simple Linear Regression and Multiple Linear Regression methods via JASP0.18.33.0 for Windows. The results indicate that: 1) There is an influence of authoritarian parentingon Sibling Rivalry (r = 0.208 and p < 0.05); 2) There is an influence of emotional regulation onSibling Rivalry (r = 0.364 and p < 0.05); 3) The combined effect of authoritarian parenting andemotional regulation on Sibling Rivalry is not significant (r = 0.371 and p > 0.05), indicating thatthere is no effect of authoritarian parenting and emotional regulation on Sibling Rivalry amongadolescents in the Tebet sub-district